2018
DOI: 10.1016/j.compbiomed.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microvascular blood flow and oxygenation: Discrimination between two haemodynamic steady states using nonlinear measures and multiscale analysis

Abstract: Objective: This study investigates the feasibility of the use of nonlinear complexity methods as a tool to identify altered microvascular function often associated with pathological conditions. We evaluate the efficacy of multiscale nonlinear complexity methods to account for the multiple timescales of processes modulating microvascular network perfusion. Methods: Microvascular blood flux (BF) and oxygenation (OXY: oxyHb, deoxyHb, totalHb and SO2%) signals were recorded simultaneously at the same site, from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…So, the length of each time series { y τ } is equal to the length of the original signal divided by the scale factor, τ. At the coarse‐grain of 24 scales, the signal length is 1000 which we show in is sufficient for complexity analysis. The LZC was calculated for each coarse‐grained sequence as a function of the scale factor, τ, and the MLZC was evaluated.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…So, the length of each time series { y τ } is equal to the length of the original signal divided by the scale factor, τ. At the coarse‐grain of 24 scales, the signal length is 1000 which we show in is sufficient for complexity analysis. The LZC was calculated for each coarse‐grained sequence as a function of the scale factor, τ, and the MLZC was evaluated.…”
Section: Methodsmentioning
confidence: 91%
“…Above the scale corresponding to the heart rate of the individual time series, the relatively periodic oscillatory influence will be diminished and the signal contains more information. To reach higher scales, longer recordings are required and we have shown that there is a lower limit on the number of samples required to achieve repeatable and accurate complexity analysis limiting the lowest frequency cutoff. We observed different scales at which the maximum separation between groups occurred with DM0‐DM1 and DM0‐CB at scale τ = 15 and DM1‐CB at τ = 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the number of unique patterns in the time series or model order; (ii) how hard it is to create or compress the information without loss; and (iii) the degree of organization or structure in LDF( t ). The most widely used measures used in LDF signal analysis are Lempel–Ziv complexity (LZC), sample entropy and effort‐to‐compress complexity (Thanaj, Chipperfield, & Clough, ). However the complexity is estimated, it provides a measure of the information content of a signal (Tigno et al., ), and for brevity, only LZC (Lempel & Ziv, ) will be considered here.…”
Section: Information and Complexitymentioning
confidence: 99%
“…At scale factor one, the time series y 1 is the original signal, and the length of each coarse‐grained time series {yτ} is equal to the original signal divided by the scale factor, τ. In previous work, we have investigated the length of signal required to obtain viable complexity measures and reported that a signal length >1000 samples is required (Thanaj et al., ), which equates to 10 min captured at 40 Hz at scale τ=24.…”
Section: Frequency Complexity and Scalementioning
confidence: 99%